Age-specific fecundity of the Beverly herd of barren-ground caribou - Thomas, Donald C.; Barry, Samuel J. (Rangifer, 1990)
The age-specific fecundity of the Beverly herd of barren-ground caribou (Rangifer tarandus groenlandicus) was monitored each winter from 1979-80 through 1986-87. Fecundity in 840 females increased with age from 12% in yearlings to 86% at age 5 years and it did not decline in old (> 11 yr) females. Significant variations occurred among winters and even between two subherds in one winter. Reproductive abnormalities were detected in 2 of 840 females and a probable resorption in 1 of 420 females collected in March. Only about 5% of the fetuses were conceived late, possibly by repeat ovulators. Combining survival and fecundity data yielded age-specific calf production, which indicated that, for example, 54% of calves were born to females 3-6 years old.